2015
DOI: 10.1093/eurpub/ckv147
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence among patients with chronic conditions in Italy

Abstract: The findings emphasize the need for improving information for the individuals affected by chronic diseases concerning the risks of non-adherence in order to encourage responsible behaviour to prescribed medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 31 publications
4
35
1
1
Order By: Relevance
“…In accordance with our study, Ma et al and Napolitano et al revealed that higher education is associated with higher adherence (25,26). It is probably due to having more awareness regarding the importance of regular taking of medications and self-care among patients with higher education.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with our study, Ma et al and Napolitano et al revealed that higher education is associated with higher adherence (25,26). It is probably due to having more awareness regarding the importance of regular taking of medications and self-care among patients with higher education.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that the participants used in average 4.2 regular drugs is in line with other studies reporting on persons with chronic conditions using in average 3-5 regular drugs. [19][20][21] Only a third of the participants in our cohort used oral spasmolytic drugs regularly, even though nearly 80% of them reported at least some level of spasticity. The explanation could be that mild spasticity can have a positive impact on functionality, or the fact that the most common oral spasmolytic drugs come with undesirable side effects as sedation and dizziness.…”
Section: Discussionmentioning
confidence: 84%
“…Poor adherence is associated with a higher residual cardiovascular risk (for the patient) and a high healthcare burden, due to greater effort to improve BP with additional diagnostic tests and interventions, such as renal denervation (RDN) . Previous cross‐sectional studies published information on factors of nonadherence in patients with hypertension . However, almost all studies on adherence in hypertension are based on the self‐assessment Morrisky questionnaire; a method shown to overestimate adherence and to be potentially biased.…”
Section: Introductionmentioning
confidence: 99%